Reconsidering Nietzsche and Politics. Issue 3 (1st September 2020) - McCall, Corey
ABSTRACT: A review of two distinctive yet, in the end, complementary approaches to reviving Nietzsche as a political thinker beyond his early reception as a prophet of National Socialism or subsequently as an apolitical thinker.